OTOMATISASI PENGATUR SUHU DAN WAKTU PADA PENYANGRAI KOPI ( ROASTER COFFEE ) BERBASIS ATMEGA 16 PADA TAMPILAN LCD ( LIQUID CRYSTAL DISPLAY ) - Ristiawan, Masde; Ariyanto, Eko (Vocational School Diponegoro University, 2016)
Masde Ristiawan, Eko Ariyanto Roasting is one of the most important processes in processing coffee beans. So it takes an automatic coffee roaster machine that can support the home roasting process. Basically, this coffee roaster is a heating device, the temperature is regulated following the input setpoint. The heating process is produced by electric heating elements which are controlled by the relay. The temperature sensor used is K type MAXX 6675 Thermocouple. The minimum system of ATmega 16 is used as the overall system control, Users can monitor temperature values and timers, which are displayed via the LCD display. In roasting coffee, roasting weight and temperature are very influential in the length of roasting time. Maximum capacity of 350 gram coffee roasters. To roast coffee with a weight of 100 grams at a temperature of 100 Â° C it takes 34 minutes for light maturity and a temperature of 130 Â° C with the same weight takes 18 minutes.Â Keywords : Thermocouple, Relay, Temperature, Sistem Minimum ATmega 16, LCD, Roaster Coffee.ReferencesSutanto, N. (2012). Rancang Bangun Coffee Producting Machine. Surabaya: Universitas Wijaya Putra.Wijaya, A. (2011). Rancang Bangun Alat Pemanas dan Pengaduk Terintergrasi dengan Temperatur dan Kecepatan Terkendali Berbasis Mikrokontroler. Depok : Universitas Indonesia.Perdana, Y. (2012). Rancang Bangun Alat Penyangrai Kacang Tanah dengan Penggerak Motor DC Berbasis Mikrokontroler AT89s51. Jakarta: Universitas Negeri Jakarta.Kurniawan, R. (2014). Sistem Pengendalian Suhu Menggunakan Metode Fuzzy Logic Pada Tungku Mesin Penyangrai Kopi. Jember : Universitas Jember.Amiq, B. (2015). Rancang Bangun Alat Penyangrai Kopi Semi Otomatis dengan Kapasitas 5Kg. Surabaya: Universitas Negeri Surabaya.Hartanto, S. (2012). Prototipe Pintu Bendungan Otomatis Berbasis Mikrokontroler ATmega 16. Yogyakarta: Universitas Negeri Yogyakarta.Kholatingulloh, T. (2015). Otomatisasi Pengatur Suhu dan Waktu Pada Oven Listrik Berbasis arduino yang ditampilkan pada LCD. Semarang: Universitas Diponegoro.